ANALISIS PESAN DAKWAH PADA LAGU HYMNE MASYARAKAT INDONESIA MEMBANGUN (MIM) BAGI MAHASISWA KOMUNIKASI DAN PENYIARAN ISLAM IAI AL-AZIS - Fithriyana Sabrina; Elang Bakhrudin; Anjar Sulistyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
It is important to package and utilize media that act as appropriate intermediaries when conveying a message or information to ensure that there are no interruptions during delivery and that the meaning of the message is not easily altered once received. There are two ways to convey messages: directly or through communication media. The material conveyed can be in the form of guidance, knowledge, and entertainment. The song Masyarakat Indonesia Membangun is a song by Syaykh Al zytun containing a high value of da'wah content, but many students do not know it. The purpose of this research is to explore the values that exist in the MIM Hymn song with the Roland Barthes theory approach. The values obtained are disseminated to students and find out students' perceptions of the meaning and messages contained in the Indonesian Community Building Hymn song. This research method uses a descriptive qualitative approach. The primary data sources in this study are friends of the songwriter and IAI AL AZIS students class of 2021 to find out their perceptions of the messages and meanings conveyed by the researcher after listening to the MIM Hymn song. In addition, direct observation was carried out when exploring student perceptions, becoming part of primary data collection. Secondary data sources were obtained from books, articles, and related scientific journals. The results of the research on this MIM Hymn song in terms of Roland Barthes' theory have three meanings, denotation, connotation and myth. The denotation meaning is found in the sentence faith, god, I build, society, building, main work. The connotation meaning is found in the sentence container. And the mythical meaning is found from the results of the connotation sentence. As for students' perceptions of the meaning of the message of the Indonesian Community Building Hymn that they feel this song is very suitable to apply in everyday life. Many students are inspired and motivated to carry out the national spirit in development and are ready to make changes in accordance with the two stanzas of the Hymn Indonesian Community Building song. Key word: Analysis of da'wah messages, songs, students;